The Impact of Terminal Values and Yellow Press on Consumer Behavior - Andrea Gröppel-Klein; Claas Christian Germelmann (European University Viadrina, Department of Business Administration and Economics, 2005)
We investigate if pluralistic consumption styles (like "frugality", or "indulgence in luxury") can be identified and are correlated with different terminal values and if values and consumption styles prove to be stable or can be changed by drastic events. The results of two polls (before and after the war in Iraq) are compared. Using content analyses, media influence on consumers' values and consumption patterns is also analyzed. Marketing relevance of the research is substantiated by investigating whether values and/or specific consumer trends have a significant impact on the preference of advertising campaigns showing different lifestyle themes.
Keywords: 330; Konsumentenverhalten; Lifestyle; Soziale Werte; Kommunikationsmedien; Werbewirkung; Schätzung; Deutschland